Optimization Normal Delivery through Birth Preparation Center with Enhancement Physical Readiness of Pregnant Women in Purwosari Village, Sayung District, Demak Regency - Arum Meiranny; RR. Catur Leny Wulandari (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Pregnancy and childbirth are very memorable experiences for a woman. As many as 90% of pregnant women do not physically prepare to give birth normally, so the side effects that occur are that the mother is not strong enough, gets tired quickly, has no energy, so she decides to give birth by caesarean section faster. The number of pregnant women who had a gestational age of more than 20 weeks in the Purwosari Village Area is 25 people. Pregnant women did’t have good knowledge about normal delivery and didn’t have good physical readiness to give birth normally, due to lack of information. The solution to this problem aims to increase the knowledge and physical readiness of pregnant women so that they can give birth normally through the Birth Preparation Center. Implementation of activities with the application of science and technology which was carried out twice, on June 5, 2021 and July 6, 2021, with the target of pregnant women in Purwosari Village, Sayung District, Demak Regency. The form of transfer of science and technology begins with a pre-test and ends with a post-test, education is delivered in an easy-to-understand method, namely providing material about the physical readiness of pregnant women. All participants also immediately practiced pregnancy exercises at the time of implementation according to the instructions from the proposing team. In addition, fellow participants also discussed and exchanged experiences about their pregnancy. Participants' knowledge about normal delivery increased by 87%, participants felt more prepared to give birth vaginally. The most important thing in this activity is that the mother would teach other pregnant women.